1962
DOI: 10.1029/jz067i003p01085
|View full text |Cite
|
Sign up to set email alerts
|

Vertical migration of particles in front of a moving freezing plane

Abstract: A principle of particle segregation by freezing is presented. It is demonstrated experimentally by means of a transparent freezing cabinet in which a sample of distilled water freezes from the bottom upward. In this way the freezing front line travels vertically and the particles are carried against gravity. By use of the same material with different shapes (glass beads and broken quartz or glass) it is demonstrated that an important factor in particle migration is the shape of the particle or its contact area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

1968
1968
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(63 citation statements)
references
References 1 publication
4
59
0
Order By: Relevance
“…Rowell and Dillon (1972 ) made the add!J:ional observation that the formation of bands of air bubbles parallel to the freezing front also played a central role in the incorporation of clay-rich layers in those cases where solutions containing suspended, dispersed clays were frozen . Similar to both the electrolyte and the dissolved gas, and in accordance with the work of Corte (1962) and Wilcox (1980) cited above, dispersed clay particles were observed to migrate in front of the advancing freezing front, but only until gas precipitation occurred. At this point, debris was trapped within the bubbles and thereby incorporated into the ice.…”
Section: Gas Nucleationsupporting
confidence: 57%
See 2 more Smart Citations
“…Rowell and Dillon (1972 ) made the add!J:ional observation that the formation of bands of air bubbles parallel to the freezing front also played a central role in the incorporation of clay-rich layers in those cases where solutions containing suspended, dispersed clays were frozen . Similar to both the electrolyte and the dissolved gas, and in accordance with the work of Corte (1962) and Wilcox (1980) cited above, dispersed clay particles were observed to migrate in front of the advancing freezing front, but only until gas precipitation occurred. At this point, debris was trapped within the bubbles and thereby incorporated into the ice.…”
Section: Gas Nucleationsupporting
confidence: 57%
“…During the process, Corte seeded the advancing front with particles of various densities, sizes and shapes, and subsequently analysed the ice cores for evidence of preferential clast rejection in terms of the debris character and the freezing rates involved. He reported a crude inverse relationship between the freezing rate and the maximum size of particles forced ahead of the ice, and also that the shape of any particle, through its influence on the ratio of mass-tocontact area, played a role in the process such that "increasing the con tact area of the particle while the size is constant causes the migration to increase" (Corte, 1962). Theory and modelling of the forces which result in individual particle rejection at the freezing interface have validated these observations.…”
Section: The Influence Of Freezing Rate On the Physical Properties Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases the solid}liquid interface deforms around the particle, thereby trapping it within the growing solid region. If the solidi"cation rate is slow and the The dependence of the solidi"cation-front behaviour on the particle size and solidi"cation velocity was "rst reported by Corte [3]. Corte's interest in the frost-heaving characteristics of soils motivated him to perform a series of experiments in which he investigated the interaction of the ice}water interface with particles made of a variety of di!erent geological materials.…”
Section: Introductionmentioning
confidence: 99%
“…Under typical conditions, solidification takes place along the lower (or warmer) boundary of an ice lens for a finite period of time before a new lens forms beneath it and traps the layer of partially frozen sediments in between. In an effort to learn more about the controls on analogous behavior in a simpler system, Corte (1962) initiated a series of experiments to investigate the interaction of an ice-liquid interface with a single particle. The importance to the materials processing industry motivated much further study, leading to a general consensus on the major stages of behavior that are shown schematically in Figure 3.…”
Section: Rejection and Trappingmentioning
confidence: 99%